The effect of decarburized layer on rolling contact fatigue of rail materials under dry-wet conditions. (September 2018) - Zhao, X.J.; Wang, H.Y.; Guo, J.; Liu, Q.Y.; Zhao, G.T.; Wang, W.J.
Abstract: Decarburization means carbon in rail material lost in the hot rolled process. It changes the microstructure of rail materials and will influence their rolling contact fatigue (RCF) characteristic. The objective of this study is to explore the effect of decarburized layer on rolling contact fatigue and propagation mechanism of crack under the wet condition using a rolling-sliding wear testing machine. The results show that the crack growth rate on the decarburized rail roller is over 4 times than that on the non-decarburized rail. Small pitting presents on the non-decarburized rail roller, which is dominated by transgranular crack. While, long mouth surface crack dominates on the decarburized rail roller and the cracks mainly grow along the ferrite line or the grain boundary. With the cycles increasing, the surface cracks of decarburized rail roller gradually break and forms spalling damage, eventually expands to bulk spalling. Meanwhile, the crack growth mechanism changes back to the transgranular propagation and propagates in depth with a large angle when the decarburization is worn off. Highlights: The surface damage aggravates when the decarburization gradually worn off. Decarburization has large influence on the growth rate of fatigue cracks. Crack mainly grows along the ferrite line or the grain boundary in decarburized rail. Crack angle in pearlite is larger than which in ferrite.